Organic and inorganic light-emitting diodes for photodynamic therapy of cutaneous leishmaniasis - Saydulla Persheyev; Ifor Samuel; Terry Smith (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2023)
For effectively fighting worldwide infectious diseases such as cutaneous leishmaniasis, novel approaches are required. Photodynamic Therapy (PDT) is one such possibility. PDT involves applying a light-sensitive chemical (photosensitizer), which should be highly efficient, non-toxic, and work at longer light wavelengths. This photosensitizer needs to be activated by a light source that provides uniform emission over a large area, high intensity, easy to fabricate, compact, and low cost. In this work, we designed and built light sources based upon commercially available Organic Light Emitting Diode (OLED) and LED parts to experimentally validate the combination with methylene blue photosensitizer to kill Leishmania major and Crithidia fasciculata cells in vitro. Our results showed that suitable-sized OLEDs, as compact and uniform light sources, are very good candidates for photodynamic therapy and can be used to efficiently kill such kinetoplastids in vitro. Therefore, it has real potential to be used in wearable devices for ambulatory treatment of patients.